Beer lees and ceramsite amendments enhance the two-stage co-composting of green waste. (September 2021) - Bai, Yifan; Zhang, Lu; Yin, Zexin; Sun, Xiangyang
Highlights: ·Beer lees and ceramsite were used as amendments in green waste (GW) composting. ·Combined addition of beer lees and ceramsite promoted the degradation of GW. ·Optimized physicochemical and microbial properties explained the rapid decomposition. ·Addition of 25% beer lees and 15% ceramsite reduced the composting time to 20 days. Abstract: Composting is a major way to process green waste (GW), and amendments are important in GW composting. In this study of the two-stage co-composting of GW, beer lees (0, 25, 30%) and/or ceramsite (0, 10, 15%) were assessed as amendments. Changes in bulk density, porosity, temperature, pH, gaseous emissions, dissolved organic carbon (DOC) and nitrogen (DON), lignocellulose degradation, microbial abundances, and phytotoxicity were assessed during GW composting with the amendments. Treatments with a combination of beer lees and ceramsite had positive effects, and 25% beer lees and 15% ceramsite optimized all compost parameters. The optimal combination of amendments extended the thermophilic phase, enhanced the lignocellulose decomposition, and generated a stable and mature product in 20 days. Consequently, the best final compost was not phytotoxic (germination index: 164%), was mature (void space ratio: 48.48, pH: 7.20, and DOC/DON ratio: 0.51), and nutrient-rich (especially for N: 5.13%, P: 1.84%, and K: 0.68%).